Avian transcriptomics: opportunities and challenges - Jax, Elinor; Wink, Michael; Kraus, Robert H. S. (Journal of ornithology, 2018)
Recent developments in next-generation sequencing technologies have greatly facilitated the study of whole transcriptomes in model and non-model species. Studying the transcriptome and how it changes across a variety of biological conditions has had major implications for our understanding of how the genome is regulated in different contexts, and how to interpret adaptations and the phenotype of an organism. The aim of this review is to highlight the potential of these new technologies for the study of avian transcriptomics, and to summarise how transcriptomics has been applied in ornithology. A total of 81 peer-reviewed scientific articles that used transcriptomics to answer questions within a broad range of study areas in birds are used as examples throughout the review. We further provide a quick guide to highlight the most important points which need to be take into account when planning a transcriptomic study in birds, and discuss how researchers with little background in molecular biology can avoid potential pitfalls. Suggestions for further reading are supplied throughout. We also discuss possible future developments in the technology platforms used for ribonucleic acid sequencing. By summarising how these novel technologies can be used to answer questions that have long been asked by ornithologists, we hope to bridge the gap between traditional ornithology and genomics, and to stimulate more interdisciplinary research.